Application of functionalized Fe3O4@SiO2 nanoparticles as an adsorbent for heavy metal removal - Mehrdad Zarabadipour; Majid Soleimani; Majid Ghahraman Afshar (Results in Chemistry, 2025)
This is a piece of novel work to apply magnetic nanoparticle to remove heavy metal ion including cadmium and copper. According to the great properties of this nanoadsorbent such as high selectivity and great adsorption-desorption life cycle, this approach has a potential to be applied in water and waste water treatment plant. In the present study, Fe3O4@SiO2 nanoparticles functionalized with dendrimer polymer molecules are synthesized using co-precipitation method. Afterwards, the synthesized nanoparticle is subjected for the extraction of Cu(П) and Cd(П) ions from aqueous solutions. Surface chemistry, particle size and morphology of synthetic nanoparticles are evaluated using transmission electron microscope (TEM), scanning electron microscope (FE-SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), vibrating sample magnetometer (VSM), thermogravimetric analysis (TGA) and X-ray energy diffraction (EDX). The extraction parameters such as contact time, adsorbent dose, pH and initial ion concentration are optimized to investigate the performance of the adsorbent. The maximum adsorption capacity of Cu(П) is obtained at 0.45 mmol/L at the initial concentration, 16 mg adsorbent dose, pH 7 and contact time of 18 min. Additionally, the maximum adsorption capacity of Cd(П) is obtained at 0.3 mmol/L initial concentration, 16 mg adsorbent dose, pH 7 and contact time of 20 min. Moreover, the maximum adsorption capacity of Cu(П) and Cd(П) are 99.7 and 115.7 mg/g, respectively. These nanoparticles are capable to be reused in successive cycles of adsorption-desorption for 8 times without a significant decrease in activity. The adsorption process is well explained by the Langmuir adsorption isotherms which is based on a single-layer adsorption. According to the calculated parameters, the kinetic data fit well with the pseudo-second-order kinetic model which shows the chemisorption process of the main adsorption step. The prepared nanoadsorbent indicates an excellent adsorption efficiency which make it suitable in the field of water purification. In addition, the synthetic adsorbent possesses the ability of separation by applying a magnetic field in the aqueous solution.